The Right on Land for Foreigner and Foreign Legal Entity Tourism Investasion Perspective, Participation and Nominee Practice Prevention - IGN. Supartha Djelantik; I Nyoman Putu Budiartha; Hartini Saripan (Warmadewa Press, 2022)
Bali is one of the national cultural heritages, which is endlessly praised in various essays and research results, then becomes a reference and promotion as an exotic island that inspires the rise of world tourism. Tourism encourages investment in hospitality, restaurants, transportation, trade, property, the creative economy sector and others. Investment, changing the function of agriculture into hospitality and transforming the work of farmers into services. Major changes in the mind-set of rural farmers to urban services. This change is not accompanied by a significant expansion of public participation, because tourism is concentrated in capital due to legal limitations that favoring on investors. The government is trying to make corrections, through the following steps, namely: (1) through ASEAN economic cooperation, Indonesia-Australia bilateral cooperation (IA-CEPA) and other countries, (2) deregulation in the fields of investment, land by granting usufructuary rights over land; and (3) encourage community participation through agrarian reform. These steps are important means, as a trigger for the awakening of the awareness of the basis of national economic development which Article 33 paragraph (1) of the 1945 Constitution of the Republic of Indonesia, determines that